Multi-omics revealed the promoting effect of dietary inulin supplementation on hepatic gluconeogenesis in goats - Zhu, Dan; Hu, Yun; Liu, Yong; Zhou, Chuanshe; Tan, Zhiliang; Kang, Jinhe; Wang, Zheng (Frontiers in Animal Science, 2025)
IntroductionGluconeogenesis is the primary pathway for ruminants to obtain energy. Enhancement of gluconeogenesis can significantly improve the growth performance of ruminants. Inulin, a prebiotic, has capabilities such as fostering a healthier gut microbiota and modulating metabolism. However, the application of inulin in ruminant feed is still very limited.MethodsEighteen healthy Xiangdong black goats (body weight 9.0 ± 0.19 kg) were randomly divided into two groups: the control group and the inulin group, with nine goats in each group. The inulin group used 18.9% inulin instead of normal corn. The total experimental period was 28 days, with 7 days for adaptation before the formal experiment.ResultsInulin supplementation significantly increased (P < 0.05) phosphoenolpyruvate carboxyl kinase (PEPCK) and glucose-6-phosphatase (G6Pase), as well as the expression of forkhead box protein O1 (FoxO1) in goat livers. At the same time, the serum insulin levels were significantly reduced (P < 0.05). Analysis of rumen microbes and rumen VFA levels revealed that the abundance levels of short-chain fatty acid-producing bacteria (Lachnospiracea, Blautia, Prevotella-1, and Pseudobutyrivibrio) and propionic acid concentration were significantly higher (P < 0.05) in the inulin group. Liver metabolites were analyzed via LC-MS, and increased levels of metabolites associated with the tricarboxylic acid (TCA) cycle and amino acid metabolism were observed following inulin administration.DiscussionInulin promotes the process of gluconeogenesis in goat liver by regulating the two key pathways of rumen microorganisms and liver metabolites to increase gluconeogenesis substrates.